Skills Society and Cognition Policies in the Formation of Teachers - Dias, Rosimeri de Oliveira; Kastrup, Virginia (Paidéia (Ribeirão Preto), 2013)
This study analyzes the formation of teachers and its relationships with the skills society. According to Sennett the skills society appears in the capitalism mutations and brings within it the notion of portable potential ability, stimulating the workers, so they can cope with acceleration and the short-term of information. The investigation distinguishes two cognition policies in the formation of teachers: (in)formation and (trans)formation, which co-exist. The first is based on information and connects knowing with the transmission and processing of symbolic representations. The second is grounded in experience and highlights the inseparable relationship between knowledge and invention. The study suggests that the processes which reduce formation to training and information, aiming for the development of abilities and competences, consider formation as the acquisition of knowledge ready to be consumed. In another direction, training is an inventive process, which is based on problematization and the knowledge construction experience.